Analysis of Magnetohydrodynamic Jeffery-Hamel Flow in a Convergent-Divergent Channel using Cu-water Nanofluid - Das, Ashik Chandra; Nasa, Qazi Novera Tansue; Alam, Md Sarwar (Journal of Engineering Science, 2021)
The present study focused on the entropy generation as well as the heat transfer rate and velocity profiles of a nanofluid of the Jeffery-Hamel flow, especially for convergent-divergent channels. First, the governing dimensional partial differential equations have been transformed into a system of non-dimensional ordinary differential equations. The Power series method has been used to solve these non-dimensional governing equations and the Hermite-Pade approximation has been applied for analyzing them. The effect of various physical parameters such as channel angle, Reynolds number, Hartmann number, nanoparticle solid volume frictions and Eckert number have been investigated for the velocity profiles, heat transfer and entropy generation. Here, Cu has been used as the solid nanoparticle and water has been used as the base fluid. It is interesting to remark that the entropy generation of the whole system increased at the two walls and a significant effect could be noticed on the heat transfer rate and velocity profiles. Journal of Engineering Science 12(2), 2021, 79-92